Rab10 regulates phagosome maturation and its overexpression rescues Mycobacterium-containing phagosomes maturation - Cardoso, Carla M. P. (2011)
Phagosome maturation follows a defined biochemical program and, in the vast majority of cases, the microbe inside the phagosome is killed and digested. Although, an important number of pathogens, including Mycobacterium tuberculosis, which kills around two million people every year, have acquired the ability to survive, and even replicate by arresting phagosomal maturation. To identify more of the machinery involved in phagocytosis and phagosomal maturation, we investigated the function of Rab10 in engulfment and maturation of inert particles and Mycobacterium bovis bacille Calmette-Guérin (BCG). We showed that Rab10 association with phagosomes is transient and confocal microscopy revealed detectible levels of Rab10 on phagosomal membranes at very early time-points, occurring even before Rab5 acquisition. Rab10 recruitment had strong functional consequence, as the knockdown of endogenous Rab10 by RNA interference or overexpression of Rab10 dominant-negative mutant delayed maturation of phagosomes of IgG-opsonized latex beads or heat killed-mycobacteria. These results can be explained, at least in part, by the involvement of Rab10 in recycling of some phagosomal components. More importantly, overexpression of the constitutively active mutant of Rab10 partially rescued live-Mycobacterium-containing phagosomes maturation. Indeed, we found that the membrane harbouring Mycobacterium acquired early endosome antigen 1 (EEA-1), a marker excluded from phagosomes in control cells. Altogether these results indicate that Rab10, acting upstream of Rab5, plays a prominent role in phagolysosome formation and can modulate Mycobacterium-containing phagosomes maturation.